Multidisciplinary teaching of variable complex functions in heat flow systems. - Gago, Eduardo Alberto; Szekieta, Paola Andrea; D'Alessandro, Lucas Iván (WSEAS, 2024)
In the context of new curriculum designs in engineering careers, new lines of work are being developed in teaching to achieve the development of basic competencies, acquisition of skills, and the replacement of old learning paradigms with new didactic techniques that are currently applicable. These characteristics in teaching are consolidated when they are added to the integration of knowledge in the teaching-learning process and the inclusion of computer resources. In the present work, the use of new pedagogical methodologies and diverse didactic strategies has been implemented, aiming at multidisciplinary work in the development of the topic of Complex Variable Functions corresponding to the Advanced Calculus subject in the Mechanical Engineering program. The didactic proposal presented corresponds to a system related to heat transfer in an incompressible fluid, where the concepts of complex field and fluid flow are approached analytically and graphically, giving meaning to the curricular contents, and facilitating the interpretation and conceptualization of the theory.
Keywords: Ingeniería mecánica; Cálculo avanzado; Enseñanza de la matemática; Transferencia de calor; Variable compleja